PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERS HEADS TODETHER (NHT) UNTUK MENINGKTKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 02 AMPEK ANGKEK - Rani Asna; Isnaniah Isnaniah; Enni Enni (Universitas Pahlawan Tuanku Tambusai, 2022)
Mathematics is a science that has very broad applications in all aspects of life. So much mathematics education has been developed in human life, but until now mathematics is still a subject that is less desirable and preferred by some students, because students generally think that mathematics is a difficult subject. Mathematics is considered difficult because mathematics is a science full of boring calculations and formulas, mathematics is also difficult to communicate because it is formed with symbols, is abstract in nature, and lacks communication, especially oral communication. It can be seen that the lack of maximum student learning outcomes in mathematics. This study aims to improve students' mathematics learning outcomes at SMPN 02 Ampek Angkek by applying a cooperative learning model with numbers heads to each other. The problem in this study is that the mathematics learning outcomes of class VIII students of SMPN 02 Ampek Angkek are still relatively low because they are still below the minimum completeness criteria (KKM). This type of research is classroom action research which is carried out in two cycles in the odd semester of the 2022/2023 school year. The subjects of this study were class VIII.2 students of SMPN 02 Ampek Angkek with a total of 27 students. The instrument of this research is to use observation, and test results of learning. After the data is obtained, an analysis is carried out by looking at the activeness of students in each cycle and by using the percentage of learning outcomes. The research results obtained before the implementation of the Numbers Heads Todether (NHT) type learning model, with the average student learning outcomes on test 1 is by looking at one of the student learning outcomes that the criterion value of 0% increases to 40.74% with very good criteria. Keywords: learning outcomes, mathematics, the Numbers Heads Together model